"Ma'had Aly An-Nur II Curriculum’s Role in Enhancing Yellow Book and Sharaf Literacy at An-Nur II Al-Murtadlo" - maruf awaludin (JURNAL PENELITIAN DAN EVALUASI PENDIDIKAN, 2025)
This research examines the influence of the Ma'had Aly An-Nur II curriculum on various aspects of the An-Nur II community, assessing the extent of its impact. Pesantren are often perceived as using outdated methods and resisting modernization, which can limit progress. However, adapting to an increasingly advanced era brings many benefits when done with careful understanding and preparation, avoiding negative influences. Ma'had Aly, though operating within a pesantren setting, embraces modern perspectives while preserving traditional values. This is supported by a well-designed curriculum developed with expertise, strategic planning, and clear target scope. Findings show that the curriculum plays a central role in shaping organizational performance. The case of An-Nur II can serve as a model for pesantren in balancing modernization with the preservation of their mindset and traditions.